Using a multisectoral approach in tackling child sexual abuse: lessons from a Zimbabwean case study - Muridzo, Noel G.; Chikadzi, Victor (Unisa, 2021)
Child sexual abuse is one of the prevalent social ills that affect children in Zimbabwe. In response to the problem of child sexual abuse and the need to mitigate its adverse effects, Zimbabwe established the Victim Friendly System. The Victim Friendly System is a multisectoral forum made up of social workers, medical doctors, nurses, the police force and role players within the justice system such as magistrates, prosecutors, counsellors, educationists and psychologists. These professionals offer distinctive but complementary interventions to child survivors of child sexual abuse. This paper discusses the merits and lessons gleaned from using the Victim Friendly System as a multisectoral forum to tackle child sexual abuse. In researching this phenomenon, the study adopted a qualitative approach and data were collected from 38 participants and 4 key informants selected using theoretical and purposive sampling respectively. A total of 300 court files of child sexual abuse cases were also reviewed. The findings that emerged from the study show that a multisectoral approach to dealing with child sexual abuse provides the benefit of integrated service delivery. Improved outcomes for victims of sexual abuse as well as streamlined, effective and efficient operations for organisations that form part of the Victim Friendly System were also evident. This notwithstanding, the paper also discusses some areas of concern that could potentially affect how the Victim Friendly System multisectoral arrangement works. The lessons that emerged from the study provide some insights that are useful in informing guidelines for multisectoral arrangements.